Design, simulation, and performance-evaluation-based validation of a novel RFID-based automatic parking system. (May 2020) - Salah, Bashir
Automated parking systems play an important role in improving the utilization of parking facilities, particularly in busy public areas that receive many visitors, such as airports, government buildings, and shopping malls. The current parking facilities of airports in Saudi Arabia use barrier gates and ticket-issuing machines. Such parking facilities increase the waiting time at every circulation point, especially at the entry and exit terminals, and when a large number of vehicles are waiting in the queue. In this study, we address this problem by applying an automated technology at the entry/exit terminals of the current parking facilities. In particular, we introduce a parking system that uses radio-frequency identification (RFID) technology for the entry and exit terminals. The basic components of the current entry/exit system and the proposed one (i.e., using RFID technology) are described in detail. Subsequently, a simulation model for the entry/exit system using Arena 14.7 is developed to evaluate the current and proposed entry/exit systems. The evaluation is based on two performance metrics: average waiting time and average number of waiting vehicles. The developed simulation model is validated using actual data through a systematic procedure. The outcome of this study shows that the proposed RFID-based entry/exit system significantly outperforms the current system. Similarly, the validated results confirm the robustness of the simulation model. Thus, it can be concluded that an RFID-based parking system will provide an effective solution for parking facilities.